Sociotechnical Vision of Education in Information Systems: Equity and Self-Directed Learning from the Global South - Bispo Jr., Esdras L.; Santos, Simone C. dos; Matos, Marcus V. A. B. De (Anais Estendidos do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Information System Education (ISE) concerns the reflection of equitable variables like gender, race/ethnicity, socioeconomic status and culture. However, addressing how to balance different sources of inequities is still an open challenge. Active learning and Self-Directed Learning (SDL) have the potential to create a more equitable educational environment, promoting more autonomy and crucial soft skills for students in our complex society. Understanding better how SDL effectively occurs in ISE students can also contribute to comprehending the potential of active learning in terms of capabilities approach (CA), a solid equity theory. Thus, this doctoral research investigated how ISE students conduct their SDL in developing countries from the CA lens. The results are structured over the perceptions of two ISE Brazilian undergraduates about their SDL trajectories, being each one from the lowest and highest socioeconomic status of their class, respectively. Interviews and other data sources helped to better situate the findings. The doctoral contributions were in (i) the use of CA as an equity theoretical framework in computing research, and computing education (including ISE), (ii) the proposition of a new concept called SDL capabilities, and (iii) a pragmatic instantiation of equity discussions in ISE (beyond other scientific contributions to Computing and Education in a general way).